2012
DOI: 10.1007/s10661-012-2632-y
|View full text |Cite
|
Sign up to set email alerts
|

Influences of urban wastewaters on the stream water quality: a case study from Gumushane Province, Turkey

Abstract: Urban wastewater in Turkey is primarily discharged without treatment to marine environments, streams and rivers, and natural and artificial lakes. Since it has been well established that untreated effluent in multi-use waters can have acute and chronic impacts to both the environment and human health, it is important to evaluate the consequences of organic enrichment relative to the structure and function of aquatic environment. We investigated the impacts of untreated municipal wastewater discharge from the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
8

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 45 publications
2
26
0
8
Order By: Relevance
“…Similar results were observed by Grieco et al (2017), Purandara et al (2012) and Bayram et al (2013) and this decrease in pH is attributed to the increase of organic matter and other wastes carried by the rains.…”
Section: Resultssupporting
confidence: 87%
“…Similar results were observed by Grieco et al (2017), Purandara et al (2012) and Bayram et al (2013) and this decrease in pH is attributed to the increase of organic matter and other wastes carried by the rains.…”
Section: Resultssupporting
confidence: 87%
“…(Taş, 2006), (Gedik et al 2010) and (Bayram et al 2013) reported some water quality parameters from Derbent Dam Lake, Fırtına Stream, and Harşit Stream, respectively which are in the same region with Melet River.…”
Section: Introductionmentioning
confidence: 97%
“…Comparando os valores de pH dos períodos seco e chuvoso, foi encontrada diferença estatística significativa (p < 0,05), onde foi observado redução do pH no período chuvoso. Esse resultado é condizente com os trabalhos de Purandara et al (2012) e Bayram et al (2013), e pode ser explicado pelo aumento de matéria orgânica e de outros resíduos carreados pelas chuvas. Além disso, o período chuvoso ocorre no verão, e à medida que a temperatura aumenta ocorre a ionização da água, o que estimula a concentração de íons de hidrogênio e a Andre Abreu Grieco et al redução no pH (Bayram et al, 2013).…”
Section: Parâmetros Limnológicosunclassified